Outpatient vs inpatient induction of labor with oral misoprostol: A retrospective study - Natalie Hallén; Mahdi Amini; Dag Wide‐Swensson; Andreas Herbst (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Induction of labor is one of the most common obstetrical procedures today, with a successively rising rate. With a limited number of hospital beds, the option of starting induction at home has gained increasing attention. The primary aim of this study was to compare the proportion of women achieving vaginal delivery and the duration of hospital stay before delivery in induction of labor with oral misoprostol starting at home and induction with oral misoprostol at the hospital, in a low‐risk population. Material and methods Women with home induction (n = 282) were individually matched to controls induced at the hospital during the same time period regarding parity, age, body mass index, labor unit and indication for induction. Results The rates of vaginal birth were similar in outpatients and inpatients (84.8% vs 86.2%; p = 0.5). Time from hospital admission to delivery in the outpatient group was significantly shorter than in the inpatient group (12.8 vs 20.6 h; p < 0.001), as was total hospital stay (2 vs 3 days; p < 0.001). There were no significant differences between the groups in neonatal or maternal outcomes. One patient undergoing outpatient induction had an unplanned home birth. Conclusions Starting induction at home reduced the time spent in hospital without affecting the vaginal delivery rate. Although underpowered to assess safety, this study did not show any differences in adverse maternal and perinatal outcomes between inpatients and outpatients. Further research is needed to evaluate the safety of outpatient induction of labor with misoprostol.